Severe Prolonged Hypothyroidism: Clinical, Anatomical, Physiological, and Metabolic Features. (5th March 2015) - Yeshayahu, Yonatan; Frizinsky, Shirly; Somech, Raz; Dubnov-Raz, Gal
Background . Hashimoto's thyroiditis usually presents with nonspecific systemic symptoms. The purpose of our study was to characterize the various properties of severe ongoing hypothyroidism and the rate of normalization following treatment. Methods . An adolescent girl with severe primary hypothyroidism was studied. Clinical evaluation, laboratory testing, brain magnetic resonance imaging, resting metabolic rate (RMR) testing, electroencephalogram, and visual field examination were performed at baseline and following treatment with levothyroxine. Results . At baseline, a significant psychomotor retardation was observed, serum thyroid-stimulating hormone concentration was 1088.4 mIU/mL. Magnetic resonance imaging showed a large intrasellar mass. Electroencephalogram was abnormal, and RMR was significantly reduced. Restoration of neurocognitive function and normalization of RMR, electroencephalogram, and laboratory tests occurred rapidly, alongside vanishing of the pituitary mass within 4 weeks of treatment. Conclusions . The various signs and symptoms of severe prolonged hypothyroidism may resolve rapidly with treatment, including the disappearance of a large pituitary mass.